Managing Decline in a Turbulent World: Designing a New Security Strategy for the European Union - Eissinger, Naomi; Enos, Philippe; Fenno, Gregory; Firoozi, Yasamine; Golomb, Michael; Guillory, Daniel; Harsch, Rina; Hubbell, Sophie; Klein, Joelle; Muilenburg, Cassandra; Nolan, Shannon; Speckhardt, Anja; et al. (My University, 2014)
The European Union is at a turning point in its approach vis-à-vis security and international relations. The 2003 European Security Strategy (ESS) laid out a vision for the EU as an important player on the global stage, encouraging the EU to become more active both in its military missions and in its humanitarian and development efforts. It envisions the EU as a critical actor in international events, working closely with like-minded nations and international organizations such as NATO and the UN. But ten years later, the world has changed. Since 2003, the world has experienced a myriad of significant international developments— widespread economic downturn, civil wars and regime change with the Arab Spring, the Euro crisis, terrorist attacks, famines, and numerous natural disasters. These events have contributed to the weakening of the Western world by diminishing the appeal of liberal capitalism, challenging the efficacy of democratic institutions, and calling into question the West’s ability to influence other countries, whether through military or civilian means. These challenges have prompted widespread isolationism and diminished resources dedicated to foreign policy and security within the EU.
Created as part of the 2014 Jackson School for International Studies SIS 495:Task Force Arista Cirtautas, Task Force Advisor; Mr. Dennis Chaibi, Evaluator; Anja Speckhardt, Coordinator.